Pancreatic pseudoaneurysm and its conundrum - Bakhshi, Girish; Baligar, Sushrut; Dutt, Aishwarya; Venkateswaran, Rajalakshmi; Gutte, Avinash; Landge, Ravi; Teja, Chettubattina Ravi (International Surgery Journal, 2021)
Rupture of visceral artery pseudoaneurysm can lead to hypovolemic shock in a patient with pancreatitis. With the advent of minimally invasive treatment techniques most of these can be managed by minimally invasive route and have excellent prognosis when timely intervention is initiated. Herewith, we reported a case of ruptured pseudoaneurysm of superior pancreaticoduodenal artery in a patient with pancreatitis who presented with haematemesis. The patient was successfully managed with coil embolization. A brief case report with review of literature is presented here.